KCa3.1 inhibition-induced activation of the JNK/c-Jun signaling pathway enhances IL-10 expression in peripherally-induced regulatory T cells - Miki Matsui; Junko Kajikuri; Kyoko Endo; Hiroaki Kito; Susumu Ohya (Elsevier, 2022)
The KCa3.1 inhibition up-regulates IL-10 expression in regulatory T (Treg) cells in the recovery phase of inflammatory bowel disease (IBD) model mice; however, the underlying signaling pathway remains unclear. We investigated the involvement of AP-1 (Fos/Jun) and NF-κB in the expression of IL-10 and its transcription factors (TFs) in in vitro-induced mouse splenic Treg cells. The pharmacological inhibition of JNK reversed KCa3.1 inhibition-induced increases in the expression of IL-10 and its TFs. The inhibition of KCa3.1 increased phosphorylated JNK and c-Jun levels. Therefore, the JNK/c-Jun signaling pathway may contribute to the KCa3.1 inhibition-induced up-regulation of IL-10 in peripherally-induced Treg cells.